Implementasi Metode Tikrar dalam Meningkatkan Kemampuan Membaca dan Menghafal Al-Qur’an: Studi pada Siswa Program Boarding - Yundi Haikal Aziz; Lukman Sumarna (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
This study aims to analyze the implementation of the Tikrar method in improving the ability to read and memorize the Qur'an among 7th-grade boarding program students at Al-Wildan Islamic School 3 BSD City. The primary focus is to evaluate the effectiveness of systematic repetition techniques in overcoming memorization retention barriers and tajwid accuracy. This research employs a mixed-methods approach with an explanatory sequential design. Qualitative data were gathered through participant observation and in-depth interviews, while quantitative data were obtained through pre-test and post-test instruments. Qualitative results indicate that the Tikrar method is implemented through three main stages: ability mapping planning, execution with intensive repetition (10-40 times), and routine evaluation through tasmi’. Quantitatively, the paired sample t-test yielded a significance value of 0.000 (p < 0.05) with a mean score difference of -14.659. These findings prove a significant improvement in students' reading and memorization abilities following the intervention. The study concludes that the Tikrar method effectively strengthens long-term memory and reading fluency, supported by a disciplined boarding ecosystem as a key factor in achieving learning targets.